Energy : - Priest, Joseph (Addison-Wesley, 1991)
The fourth edition of Joseph Priest's Energy draws heavily on the experience of instructors who used earlier editions. It is designed for environmental science courses for non-science majors and is suitable for fulfilling their science requirement.